Bile Acid Profiling Reveals Distinct Signatures in Undernourished Children with Environmental Enteric Dysfunction. Issue 12 (27th October 2021) - Zhao, Xueheng; Setchell, Kenneth D R; Huang, Rong; Mallawaarachchi, Indika; Ehsan, Lubaina; Dobrzykowski III, Edward; Zhao, Junfang; Syed, Sana; Ma, Jennie Z; Iqbal, Najeeha T; Iqbal, Junaid; Sadiq, Kamran; et al.
ABSTRACT: Background: Intestinal inflammation and malabsorption in environmental enteric dysfunction (EED) are associated with early childhood growth faltering in impoverished settings worldwide. Objectives: The goal of this study was to identify candidate biomarkers associated with inflammation, EED histology, and as predictors of later growth outcomes by focusing on the liver-gut axis by investigating the bile acid metabolome. Methods: Undernourished rural Pakistani infants ( n  = 365) with weight-for-height Z score (WHZ) < –2 were followed up to the age of 24 mo and monitored for growth, infections, and EED. Well-nourished local children ( n  = 51) were controls, based on consistent WHZ > 0 and height-for-age Z score (HAZ) > –1 on 2 consecutive visits at 3 and 6 mo. Serum bile acid (sBA) profiles were measured by tandem MS at the ages of 3–6 and 9 mo and before nutritional intervention. Biopsies and duodenal aspirates were obtained following upper gastrointestinal endoscopy from a subset of children ( n  = 63) that responded poorly to nutritional intervention. BA composition in paired plasma and duodenal aspirates was compared based on the severity of EED histopathological scores and correlated to clinical and growth outcomes. Results: Remarkably, >70% of undernourished Pakistani infants displayed elevated sBA concentrations consistent with subclinical cholestasis. Serum glycocholic acid (GCA) correlated with linear growth faltering (HAZ, r = –0.252 and –0.295 at the age of 3–6 and 9 mo, respectively, P <0.001) and biomarkers of inflammation. The proportion of GCA positively correlated with EED severity for both plasma (rs = 0.324 P  = 0.02) and duodenal aspirates (rs = 0.307 P  = 0.06) in children with refractory wasting that underwent endoscopy, and the proportion of secondary BA was low in both undernourished and EED children. Conclusions: Dysregulated bile acid metabolism is associated with growth faltering and EED severity in undernourished children. Restoration of intestinal BA homeostasis may offer a novel therapeutic target for undernutrition in children with EED. This trial was registered at clinicaltrials.gov as NCT03588013.